Interaksi Sosial di Sekolah dan Motivasi Belajar Peserta Didik: Kajian Pustaka dalam Perspektif Sosiologi Pendidikan - Khaerul Khakim; Saharuddin Zainuddin; Jalaludin (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This study is motivated by the importance of social interaction in schools as part of the socialization process that influences students’ learning motivation. This literature review aims to analyze the relationship between social interaction in the school environment and students’ learning motivation from the perspective of the sociology of education. The study employs a literature review method by examining relevant journals, books, and previous studies related to social interaction, learning motivation, and the role of schools as agents of socialization. The findings indicate that positive interaction between teachers and students, as well as among peers, can increase students’ sense of comfort, self-confidence, and willingness to participate actively in learning activities. In contrast, poor social interaction may reduce students’ enthusiasm and engagement in learning. This study concludes that social interaction plays an important role in shaping learning motivation, so schools need to create an inclusive, communicative, and supportive social environment.